Identifying and rationalizing the morphological, structural, and optical properties of beta-Ag2MoO4 microcrystals, and the formation process of Ag nanoparticles on their surfaces: combining experimental data and first-principles calculations - Fabbro, Maria T.; Saliby, Carla; Rios, Larissa R.; La Porta, Felipe A.; Gracia, Lourdes; Li, Maximo S.; Andres, Juan; Santos, Luis P. S.; Longo, Elson [UNESP] (Taylor & Francis Ltd, 2015)
We present a combined theoretical and experimental study on the morphological, structural, and optical properties of beta-Ag2MoO4 microcrystals. beta-Ag2MoO4 samples were prepared by a coprecipitation method. The nucleation and formation of Ag nanoparticles on beta-Ag2MoO4 during electron beam irradiation were also analyzed as a function of electron beam dose. These events were directly monitored in real- time using in situ field emission scanning electron microscopy (FE- SEM). The thermodynamic equilibrium shape of the beta-Ag2MoO4 crystals was built with low- index surfaces (001), (011), and (111) through a Wulff construction. This shape suggests that the (011) face is the dominating surface in the ideal morphology. A significant increase in the values of the surface energy for the (011) face versus those of the other surfaces was observed, which allowed us to find agreement between the experimental and theoretical morphologies. Our investigation of the different morphologies and structures of the beta-Ag2MoO4 crystals provided insight into how the crystal morphology can be controlled so that the surface chemistry of beta-Ag2MoO4 can be tuned for specific applications. The presence of structural disorder in the tetrahedral [MoO4] and octahedral [AgO6] clusters, the building blocks of beta-
Keywords: theoretical calculations; morphology; electron beam irradiation; beta-Ag2MoO4